An investigation of the role of the adiponectin variable domain on the stability of the collagen‐like domain. Issue 4 (July 2014) - Harris, Paul W. R.; Hampe, Lutz; Radjainia, Mazdak; Brimble, Margaret A.; Mitra, Alok K.
ABSTRACT The chemical synthesis is described of a polypeptide construct possessing both the variable and the collagen‐like domain of adiponectin, which can be used as a model system for probing the influence of the variable domain on multimerization of this important circulating hormone. Using a collagen domain repeat peptide unit derived from native adiponectin or a glutamic acid analogue was ineffective due to noncollagenous conformational properties in both cases. However, employing a collagen model peptide and linking this to the variable domain thioester peptide using native chemical ligation proved effective. The 63 residue peptide was characterized by circular dichroism and mass spectrometry which demonstrated that a collagen‐like triple‐helical structure was preserved. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 313–321, 2014.